Negative refraction in hyperbolic metamaterials - Hariharann Ravindran (Nanyang Technological University, 2022)
In this project, we will be studying the hyperbolic properties of metamaterials. Recent studies have shown that artificially structured metmaterials can exhibit astounding electromagnetic properties. We will study more on hyperbolic mematerials as they can hold both negative permeability and negative permittivty. We will observe the properties of Graphene, which is a a newfound two-layered (2D) carbon allotrope that is a reference unit for other graphitic materials and comprises of just a main layer of carbon molecules coordinated in a honeycomb grid. There are two main parts to this project, the beginning portion will discuss the fundamental concepts of negative refraction in metamaterials, while the second portion will concentrate on the differences of results between using different surface graphene conductivity models.